Penerapan Metode SQ3R dalam Pembelajaran Matematika untuk Meningkatkan Pemahaman Siswa Kelas VII.F SMP Negeri 12 Mataram - Asyiah, Siti (TSAQOFAH, 2022)
The purpose of this study was to find out: 1) To find out learning activities during Mathematics learning using the SQ3R (Survey, Question, Read, Recite, Review) method for class VII.F students of SMP Negeri 12 Mataram. 2) To find out the increase in Mathematics learning outcomes using the SQ3R method (Survey, Question, Read, Recite, Review) for class VII.F students of SMP Negeri 12 Mataram. This research is a Classroom Action Research (CAR), using two cycles through the planning, action, observation, and reflection stages. As subjects in this study were class VII.F students for the 2021/2022 academic year with a total of 31 students, consisting of 19 male students and 12 female students. The results of this study indicate that the application of the SQ3R method in learning Mathematics at the initial condition was 64.52 with an average of 73.23 and in the first cycle of students' classical learning mastery of 77.342% with an average value of 76.90. In cycle II, students' classical learning completeness was 93.55% with an average score of 80.48. Thus the SQ3R method in learning mathematics can effectively improve understanding of class VII.F student learning outcomes at SMP Negeri 12 Mataram in mathematics. Student activity in learning with the SQ3R method in learning Mathematics in cycle I obtained a score of 65 with a score of 26 in the good category. In the question, recite activities, presenting the results of group study and concluding that the learning outcomes are included in the sufficient category, while the activity of answering questions through group discussions is still in the less category. The deficiencies that existed in cycle I were corrected in cycle II. Acquisition of student activity scores in cycle II increased to 33 in the very good category, with a value of 82.50. In cycle II students can carry out SQ3R activities in learning Mathematics well. Teacher activity in learning Mathematics with the SQ3R method in cycle I was 68.57% (good enough category) and experienced an increase in cycle II of 85.71% (very good category).